Wound healing and antimicrobial activities of a spray gel of banana (Musa paradisiaca L.) peel extract in rabbit (Oryctolagus cuniculus) models - Ramaza Rizka; Yuandani Yuandani; Sumaiyah Sumaiyah (Shahrekord University of Medical Sciences, 2023)
Introduction: Musa paradisiaca peel has inhibited microbial growth and enhanced wound healing in animal models. However, the study on its effect as a dosage form is lacking. In the present study, the antimicrobial and wound-healing effects of a spray gel of M. paradisiaca peel extracts were evaluated in rabbits. Methods: The antimicrobial and wound healing activities of a spray gel were tested at different concentrations (10%, 15%, and 20%) of banana peel extract, categorized as low concentration (SGL), medium concentration (SGM), and high concentration (SGH) groups, respectively. The antimicrobial effects against Escherichia coli and Staphylococcus aureus were investigated by measuring inhibition zone diameters. Burns were inflicted on the back area of rabbits using hot steel. Macroscopic and microscopic examinations were performed. Results: The spray gel containing banana peel extract exhibited inhibition zone diameters of 14.2 ± 0.38 mm and 14.6 ± 0.21 mm against Escherichia coli and Staphylococcus aureus, respectively. SGH showed the strongest wound-healing activity of all the samples, which was comparable with bioplacenton (BG) as a positive control. The wounds healed on days 16, 16, 20, and 22 for bioplacenton, SGH, SGM, and SGL, respectively. There was a significant difference (P<0.05) in collagen density and epidermal thickness between the treatment groups and the negative control (1.2 % sodium carboxymethyl cellulose (Na-CMC)). Conclusion: The result indicates that the spray gel of M. paradisiaca peel ethanolic extract possesses antimicrobial and wound-healing activities, emphasizing its potential to be developed as a wound healing agent.